2014
DOI: 10.1179/1743132813y.0000000276
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and memory evaluation of Wistar rats exposed to 1·8 GHz radiofrequency electromagnetic radiation

Abstract: Given the results of the present study, we speculate that RF-EMR does not promote CNS impairment, but suggest that it may lead to stressful behavioral patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
2
7
0
3
Order By: Relevance
“…found that RF-EMR exposure (1.8 GHz) for 25 s every 2 min for 3 consecutive days induced neither anxiety nor impaired working memory in adult (60-day-old) rats. However, stress behaviors, including immobility time and rearing frequency, were significantly increased under these conditions20. In comparison, Ntzouni et al .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…found that RF-EMR exposure (1.8 GHz) for 25 s every 2 min for 3 consecutive days induced neither anxiety nor impaired working memory in adult (60-day-old) rats. However, stress behaviors, including immobility time and rearing frequency, were significantly increased under these conditions20. In comparison, Ntzouni et al .…”
Section: Discussionmentioning
confidence: 66%
“…RF-EMR exposure increased the time spent exploring novel objects, thus suggesting enhanced recognition memory of the familiar object. Previous studies reported that RF-EMR exposure affected emotionality and stress behavior in rats1920, and we therefore determined if the failure in object discrimination might be a function of compromised motor ability or anxiety-related responses using an open field test to measure the center distance and average speed21. We found no significant difference in spontaneous locomotor activity between RF-EMR-exposed and control mice, suggesting that RF-EMR did not cause ataxia or motor impairments under the experimental parameters used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Narayanan et al (13) indicated that mobile phone radiation could affect the emotionality of rats without affecting their general locomotion. But Júnior et al (8) have suggested that radiofrequency electromagnetic radiation from a GSM cell phone may lead to stressful behavioral patterns. Similarly, Saikhedkar et al (21) reported that there are significant differences in behavior, i.e.…”
Section: Results An Discussionmentioning
confidence: 99%
“…Одним из неотъемлемых аспектов является исключение неблагоприятного влияния на репродуктивную систему организма, как определяющую влияния излучения на последующие поколения, вместе с реакциями нервной системы, которые позволяют регистрировать острые биологические эффекты ЭМП РЧ на состояние текущего поколения. В ряде экспериментальных работ, посвященных изучению этого вопроса отмечается как наличие [3,6,7,13,14], так и отсутствие [10,11] функциональных, морфологических и молекулярных изменений со стороны нервной и репродуктивной систем животных при различных режимах воздействия ЭМП с уровнями ППЭ в несколько раз меньших величины 500 мкВт/см 2 , установленной как порог вредного действия ЭМП стандартов сотовой связи [1,5]. Также имеются единичные исследования биологического действия ЭМП РЧ стандарта DECT [4,9,12], свидетельствующие о потенциально неблагоприятном влиянии излучения на нервную и репродуктивную системы, которые вместе с противоречивыми данными о характере влияния низкоинтенсивных ЭМП стандартов связи на живые системы указывают на необходимость дальнейших исследований биологических эффектов реакций ключевых систем, определяющих состояние здоровья организма и последующих поколений, в зависимости от интенсивностно-временных характеристик ЭМП РЧ радиотелефонов стандарта DECT.…”
Section: вестник новых медицинских технологий -2015 -Nunclassified